2021
DOI: 10.1590/fst.13120
|View full text |Cite
|
Sign up to set email alerts
|

Shelf-life assessment of energy banana bar using acceleration method with critical moisture content approach

Abstract: The shelf-life of the product need to be evaluated according to the commercialization of the product. Shelf-life assessment of the product can be done using acceleration method (Accelerated Shelf-life Testing) with critical moisture content approach. This research used the acceleration method to predict the expired date of the energy bar based banana. This method required the data such as initial water content, critical moisture content, solid weight of the product, surface area of the packaging, permeability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…A disaster condition requires the stockpiled rations to be shelf‐stable for an extended period compared to routine food products. Several studies have been dedicated to evaluating the best means of accelerated shelf‐life stability calculation (Bharath Kumar & Prabhasankar, 2018; Byun et al., 2010; Darsch & Moody, 2009; Ekafitri et al., 2021; González et al., 2017; Khan et al., 2014; Mitrevski et al., 2016; Putri et al., 2021; Sefrienda et al., 2022; Sirpatrawan, 2009; Tuersuntuoheti et al., 2019; Yang et al., 1997; Zhang et al., 2016). Researches have shown that water activity has been among the most preferred methods of shelf‐life estimation for noodles and similar products (Li et al., 2011; Mitrevski et al., 2016; Putri et al., 2021; Sefrienda et al., 2022; Sirpatrawan, 2009).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A disaster condition requires the stockpiled rations to be shelf‐stable for an extended period compared to routine food products. Several studies have been dedicated to evaluating the best means of accelerated shelf‐life stability calculation (Bharath Kumar & Prabhasankar, 2018; Byun et al., 2010; Darsch & Moody, 2009; Ekafitri et al., 2021; González et al., 2017; Khan et al., 2014; Mitrevski et al., 2016; Putri et al., 2021; Sefrienda et al., 2022; Sirpatrawan, 2009; Tuersuntuoheti et al., 2019; Yang et al., 1997; Zhang et al., 2016). Researches have shown that water activity has been among the most preferred methods of shelf‐life estimation for noodles and similar products (Li et al., 2011; Mitrevski et al., 2016; Putri et al., 2021; Sefrienda et al., 2022; Sirpatrawan, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Within 24 h after production, the initial moisture content of the product ( M i ) was evaluated according to AOAC to be 12.6%. The solid weight ( W s ) of a single serving of the product was 215 g. The packaging permeability )(kx of the aluminum packaging was estimated to be 0.00386 g H 2 O/m 2 hari mmHg, the vapor pressure of pure water at 30°C was 31.80 mmHg, and the surface area ( A ) of the packaging was estimated to be 0.09 m 2 (Ekafitri et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Samples of the dehydrated chayote slices were placed inside desiccators with saturated solutions to maintain the specific relative humidity at 25 • C. The water activity range was set from 0.113 to 0.75 using different salt solutions: LiCl = 0.113, MgCl = 0.328, K 2 CO 3 = 0.432, Mg(NO 3 ) 2 = 0.529, KI = 0.689, and NaCl = 0.75 [18]. The relative humidity for each salt solution at 25 • C was around 11.1%, 32.8%, 44%, 55.8%, 68%, and 75.5%, respectively [25,26]. Samples were weighed periodically until reaching a constant weight, determined when the difference between two consecutive measurements was less than 0.5%.…”
Section: Sorption Isothermsmentioning
confidence: 99%
“…At the beginning, the literature was checked for shelf-life assessment of bar including acceleration method, as well. Thus, these temperatures were also chosen according to the literature (Corrigan et al, 2012;Çınar and Aydın, 2020;Singh et al, 2020;Ekafitri et al, 2021). Moisture content measurement was periodically done at predetermined time intervals (day 0, 1, 2, 3, 4 and 7) for five different formulations.…”
Section: Storage Studiesmentioning
confidence: 99%